A brief look at diagnosing neurocognitive disorders in a VA primary care setting: Understanding the practices of our physician partners and the future of integration. Issue 6 (22nd July 2022) - Williams, Andrea; Cottingham, Maria; Patel, Erin
Abstract: Objective: The population aged 65 and over is growing rapidly and with it are increased demands for integrative care and management of cognitive health issues. Such care models often do not include neuropsychologists or other psychology specialties. Methods: In this study, 72 medical charts of VA patients diagnosed with neurocognitive disorders were reviewed using best practice guidelines for diagnosing and managing neurocognitive disorders, adapted from Downs et al. (2006). Results: Results indicated that physicians typically used clinical judgment through review of medications, blood work within the past year, and a history of symptoms to make diagnostic conclusions. Cognitive assessment and consideration of other reversible causes of cognitive decline (e.g., depression) were less commonly considered. Conclusions: The results are discussed in terms of potential implications for neuropsychologists and the integration of neuropsychology and primary care.